T2-based temperature monitoring in bone marrow for MR-guided focused ultrasound. Issue 1 (December 2016) - Ozhinsky, Eugene; Han, Misung; Bucknor, Matthew; Krug, Roland; Rieke, Viola
Abstract Background Current clinical protocols for MR-guided focused ultrasound (MRgFUS) treatment of osseous lesions, including painful bone metastases and osteoid osteomas, rely on measurement of the temperature change in adjacent muscle to estimate the temperature of the bone. The goal of this study was to determine if T2-based thermometry could be used to monitor the temperature change in bone marrow during focused ultrasound ablation of bone lesions. Methods We investigated the dependence of T2 on temperature in ex vivo bovine yellow bone marrow at 3T and studied the influence of acquisition parameters on the T2 measurements. We examined if T2 changes in red bone marrow caused by the ablation of ex vivo trabecular bone were reversible and measured the patterns of heating and tissue damage. The technique was validated during the ablation of intact ex vivo bone samples and an in vivo animal model. Results Results of the calibration experiment showed a linear relationship (7 ms/°C) between T2 change and temperature and could be used to quantify the temperature during heating of up to 60 °C. During trabecular bone ablation, we observed a linear relationship (5.7 ms per °C) between T2 and temperature during the heating stage of the experiment. After cool down, there was residual T2 elevation (~35 ms) in the ablated area suggesting irreversible tissue changes. In ex vivo and in vivo cortical bone ablation experiments, we observed an increase in T2 values in the marrow adjacent to the intersection of the cortical bone and the beam path. The in vivo experiment showed excellent correspondence between the area of T2 elevation in marrow during the ablation and the resulting non-enhancing area in the post-contrast images. Conclusions In this study, we have demonstrated that T2-based thermometry can be used in vivo to measure the heating in the marrow during bone ablation. The ability to monitor the temperature within the bone marrow allowed more complete visualization of the heat distribution into the bone, which is important for local lesion control.